Biomarcadores nos distúrbios de coagulação e de injúria renal em pacientes acidentados por serpentes do gênero Bothrops spp. - Lopes, Nicole Coelho (2024)
In Brazil, the Bothrops spp. genus is responsible for 90% of snakebites, and acute kidney injury (AKI) is a frequent, severe, early-onset, and lethal clinical manifestation. Endothelial damage is associated with the pathogenesis of AKI, and is therefore an important mechanism for the clinical evaluation of the patient. In this context, the objective of this study is to investigate coagulation abnormalities after Bothrops envenomation and their contributions to kidney injury before and after antivenom administration. The present study was carried out between August 2022 and December 2023, and is an observational, longitudinal, and prospective study carried out with patients admitted to a referral hospital for emergency care in Fortaleza (Ceará, Brazil). Samples were recorded at three times: before antivenom administration (collection 1), 10 hours (collection 2) and 8 hours (collection 3) after serum therapy. Patients were divided into groups with or without bleeding on admission and were evaluated for the presence of AKI according to the Kidney Disease Improving Global Outcomes (KDIGO) criteria. The biomarkers Neutrophil Gelatinase-Associated Lipocalin (NGAL), Kidney Injury Molecule-1 (KIM-1), Monocyte Chemoattractant Protein-1 (MCP-1), Syndecan-1, Vascular Cell Adhesion Molecule-1 (VCAM-1), Von Willebrand Factor A2 (vWFA A2), Angiopoietins 1 and 2 were intuitively analyzed. In total, 34 patients with an interval <8 hours between the bite and the antivenom injection were included. Of these individuals, 17 had active bleeding on admission and the other 17 did not manifest this clinical sign. The bleeeding group obtained higher results for the ratio between proteinuria and creatinine, in addition to recording the highest percentage of cases with blood incoagulability. In the renal evaluation, the bleeding group expressed significantly higher levels of KIM-1 in collections 1 and 2, as well as higher concentrations of urinary NGAL in collections 1 and 3. In addition, endothelial and coagulation analysis indicated that these individuals also had higher levels of syndecan-1, angiopoietins 1 and 2, and vWFA A2. In conclusion, patients admitted with active bleeding after the Bothrops spp. accidents were those who presented significantly higher levels of non-host renal, endothelial, and coagulation biomarkers, as well as evidenced the non-renal recovery of this group, even after the administration of antibothropic serum, within the time interval studied.